Effect of a mobile application intervention on knowledge, attitude and practice related to healthy marriage among youth in Iran - Sahebjan Torkian; Firoozeh Mostafavi; Asiyeh Pirzadeh (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Mobile app education is one of the new educational models. Hence, the purpose of this study was to determine the effectiveness of mobile app intervention on knowledge, attitude, and practice of youth for a healthy marriage. MATERIALS AND METHODS: This quasi-experimental study was conducted in 2019 on 88 young people who were selected by simple random sampling in premarital counseling center of Falavarjan city (Isfahan). Then, participants were randomly allocated to an intervention and a control group. Mobile application intervention was installed on the intervention group's mobiles. Data were collected by questionnaire in two times. Data were analyzed using paired t-test and independent t-test. RESULTS: The mean (Standard deviation) of couples' age was 21.11 (5.06) years. The results showed that after the installation of educational consulting app in the intervention group, the mean score of knowledge (P = 0.001), attitude (P = 0.001), and practice (P = 0.001) after intervention were significantly higher than before the intervention. CONCLUSION: Mobile-based educational and counseling app increases couples' knowledge, attitude, and practice in premarital education. Therefore, it is recommended that this type of education (mobile app) be used to promote premarriage education classes.